Impact of Switching From Darbepoetin Alfa to Epoetin Beta Pegol on Iron Utilization and Blood Pressure in Peritoneal Dialysis Patients. Issue 5 (5th May 2015) - Washida, Naoki; Inoue, Shuji; Kasai, Takahiro; Shinozuka, Keisuke; Hosoya, Koji; Morimoto, Kohkichi; Wakino, Shu; Hayashi, Koichi; Itoh, Hiroshi
Abstract New erythropoiesis‐stimulating agents with a longer half‐life have been developed for the treatment of anemia in patients with end‐stage renal disease. This study evaluated the efficacy of darbepoetin alfa (DA) and long‐acting epoetin beta pegol (continuous erythropoietin receptor activator, CERA) in patients on peritoneal dialysis (PD). Twenty‐nine patients who had undergone PD for at least 6 months and were iron replacement‐naïve and negative for inflammatory parameters were enrolled. Hemoglobin (Hgb) levels and blood pressure were evaluated before and after switching from DA to CERA. Percent transferrin saturation (TSAT), serum ferritin levels and blood pressure were also assessed. Twenty‐eight patients were subject to the analysis, excluding one patient with a decrease in Hgb by ≥10%. Switching from DA to CERA did not alter Hgb levels. The doses of DA and CERA after 12 month treatment of each agent were 118.48 ± 79.63 and 89.88 ± 47.50 μg/4 weeks, respectively (conversion ratio, 1:0.76). The CERA dose administered during the final 6 months was abated, compared with that given during the initial 6 months (P = 0.035). The frequency of CERA injection over a 12‐month period was less than that of DA (10.0 ± 3.0 vs. 16.4 ± 5.0, P < 0.01). The conversion from DA to CERA did not alter TSAT, but decreased serum ferritin levels (from 202.69 ± 132.57 to 150.15 ± 110.07 ng/mL, P = 0.012) and systolic blood pressure (from 133.8 ± 17.3 to 129.5 ± 11.3 mm Hg, P = 0.024). In PD patients, lower doses and less frequent injection of CERA are sufficient to maintain Hgb at levels similar to those achieved by DA therapy, with improved iron utilization and reduced blood pressure.